Analysis and Impact of D-STATCOM, Static Var Compensator, Fuzzy Based SVC Controller on the Stability of a Wind Farm - Kaoutar Rabyi; Hassane Mahmoudi (Institute of Advanced Engineering and Science, 2017)
In recent years, applications of facts systems have been developed for the compensation of active and reactive power. Facts systems are electronics devices that are connected to the wind farm. This paper presents the impacts of some of these devices on the stability of a wind farm, especially D-STATCOM, Static Var Compensator and Fuzzy SVC controller. First, a presentation of D-STATCOM, SVC, then fuzzy logic controller. In simulation study, the D-STATCOM ensures the stability of the voltage and current at the point of connection with the electrical grid. Finally, Comparing the SVC to the F-SVC simulations, we notice that the F-SVC is more performed than SVC for the compensation of the active and reactive power.